DOP054 Vedolizumab in combination with steroids for induction therapy in Crohn's disease: an exploratory analysis of the GEMINI 2 and GEMINI 3 studies. (16th January 2018) - Sands, B E; Van Assche, G; Tudor, D; Tan, T
Abstract: Background: Induction therapy for Crohn's disease (CD) aims to bring patients into clinical remission rapidly. Corticosteroids (CS) are commonly used as induction agents, but safety concerns regarding their long-term use remain. Combined therapy with vedolizumab (VDZ), a gut-selective α4 β7 integrin antagonist, and ongoing CS may enhance treatment outcomes at induction. We assessed the efficacy and safety of the combination of VDZ and CS during induction therapy in patients with moderate-to-severe CD. Methods: A post hoc exploratory analysis was performed on data from the GEMINI 2 (NCT00783692) and GEMINI 3 (NCT01224171) studies, which had 6- and 10-week induction periods, respectively. Continued stable CS dosing was permitted in the studies (≤30 mg/day of prednisone or equivalent dosing with another CS). Patients who received VDZ or placebo (PLA) were stratified by CS use at baseline (CS and no-CS subgroups). Efficacy endpoints were clinical remission (defined as a Crohn's disease Activity Index [CDAI] score of ≤150 points) and enhanced clinical response (a decrease of ≥100 points in CDAI score from baseline), assessed at Week 6 (GEMINI 2 and GEMINI 3) and Week 10 (GEMINI 3). Safety endpoints included the number and incidence of adverse events (AEs). Results: In the CS subgroup, VDZ was associated with a higher rate of clinical remission than PLA at Week 6 (19.8% vs. 10.2%) and Week 10 (34.2% vs. 11.1%) in GEMINI 3 (Figure 1A). In the VDZ treatment arm, more patients in the CS subgroup achieved clinical remission than in the no-CS subgroup at Week 6 in GEMINI 2 (19.0% vs. 10.9%) and Week 10 in GEMINI 3 (34.2% vs. 22.7%) (Figure 1B). Higher rates of enhanced clinical response within the CS subgroup were seen with VDZ than PLA in both studies at all timepoints (Week 6 GEMINI 2: 36.0% vs. 18.5%; Week 6 GEMINI 3: 38.7% vs. 22.2%; Week 10 GEMINI 3: 53.2% vs. 22.2%). At Week 10 in the VDZ treatment arm, higher rates of enhanced clinical response were achieved in the CS subgroup than in the no-CS subgroup (53.2% vs. 42.3%). Incidence of AEs were similar across the groups (Table 1). Conclusions: Combined therapy with VDZ and ongoing CS may be a synergistic approach, with a similar safety profile, compared with continued CS use alone or VDZ without ongoing CS use, for induction therapy in patients with moderate-to-severe CD.